Jordan : 2008 Article IV Consultation; Staff Report; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Jordan's 2008 Article IV Consultation discusses the appropriate policy response to mounting fiscal and external vulnerabilities and higher inflation. Sharply higher world fuel and food prices led to a marked widening of the fiscal and external current account deficits and, more recently, a jump in inflation. Economic prospects remain broadly favorable, though the public and external sector imbalances imply increased challenges to sustaining strong macroeconomic performance. Structural reforms are proceeding, aimed at reducing distortions and enhancing the private sector's growth prospects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet